2011
DOI: 10.3139/217.2401
|View full text |Cite
|
Sign up to set email alerts
|

Erosion Behavior of Glass-epoxy Composites Filled with SiC from Bamboo Leaf

Abstract: The present article reports the processing, mechanical characterization and solid particle erosion response of a new class of multi phase composites consisting of epoxy resin reinforced with E-glass fiber and SiC particulates. The SiC powder synthesized from bamboo leaf employing DC extended thermal plasma technique has been used as the filler in this glass-epoxy composite. It is observed that with increasing percentage of filler particles, there is a decline in tensile and flexural strength, but there is sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…It is seen that as the content of LDS particles increases in the composite, its hardness value improves significantly. This increase in hardness with the addition of LDS may be attributed to the hard LDS particles getting pressed together with epoxy matrix and making intimate contact with each other more tightly . It is also observed that with the increase in filler content the tensile strength of composite declines gradually although the decrement is marginal.…”
Section: Resultsmentioning
confidence: 94%
“…It is seen that as the content of LDS particles increases in the composite, its hardness value improves significantly. This increase in hardness with the addition of LDS may be attributed to the hard LDS particles getting pressed together with epoxy matrix and making intimate contact with each other more tightly . It is also observed that with the increase in filler content the tensile strength of composite declines gradually although the decrement is marginal.…”
Section: Resultsmentioning
confidence: 94%
“…(b) in the composites exhibited moderately to high void content in between 0.74% and 1.02%. This may be due to the presence of irregular‐shaped marble particles which may act as a stress raiser, results in weak stress transfer among the matrix and filler particle which reduces the tensile response of the composites . The void contents in the composite may be attributed to various factors including resin property, filler shape, vacuum pressure, complex mold geometry, and resin flow rate, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…This value of hardness increased by 11.63, 18.61, and 27.91% to remain at 48, 51, and 55 Hv for the 10, 20, and 30 wt% marble dust‐filled composites, respectively. With the increased in marble dust content, the packing of the constituents in cured epoxy resin improved resulting in the improved mechanical integrity of ingredients and hence the hardness of the composite rises monotonically .…”
Section: Resultsmentioning
confidence: 99%
“…The results of the investigation reported that the improvement in the erosion resistance property of the composite depends on the weight percentage of the filler addition in the filled composites. 67…”
Section: Silicamentioning
confidence: 99%